ANTHROPOMETRIC PROFILE OF 13-14-YEAR-OLD SWIMMERS WITH DIFFERENT SPORT SPECIALIZATIONS - A.I. RYAZANTSEV1,2,3; I.N. GREBENNIKOVA; M.A. SUBOTYALOV3,4 (Паёми Сино, 2025)
Objective: To examine the morphological indicators of physique of 13-14-year-old swimmers with different sport specializations